One-pot synthesis of binary metal organic frameworks (HKUST-1 and UiO-66) for enhanced adsorptive removal of water contaminants - Azhar, M.; Abid, H.; Sun, Hongqi; Periasamy, Vijay; Tadé, Moses; Wang, Shaobin (Academic Press, 2017)
In this study, binary metal organic frameworks (MOFs) with HKUST-1 and UiO-66 have been synthesized in a one-pot process. The synthesized MOFs were characterized by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), N2 adsorption, and thermogravimetric analysis (TGA). The meso-porosity and thermal stability of the binary MOFs were higher than those of single HKUST-1 or UiO-66. The synthesized MOF hybrids were then tested for adsorptive removal of methylene blue (MB) from wastewater in terms of kinetic and isothermal adsorption as compared to a commercially available activated carbon (AC). All the synthesized MOFs showed significant removal of MB under a wide range of pH. The adsorption capacities of HKUST-1 are higher than UiO-66 and commercial AC while the binary MOFs presented an even higher adsorption capacity than single MOFs. This is the first time that binary HKUST-1 and UiO-66 MOFs have been successfully synthesized and demonstrated enhanced adsorptive removal of contaminants.